The association between Hsp70 and TNF-α as immune Response in Groupers Infected with Viral Nervous Necrosis. Issue 1 (October 2021) - Yanuhar, Uun; Arfiati, Diana; Musa, Muhammad; Sakinah Junirahma, Nur; Rahman Caesar, Nico
Abstract: Along with the increasing expansion of aquaculture in recent years, fish diseases have become a major constraint which is quite challenging for the productivity and sustainability of the aquaculture industry. Especially the attack of Viral Nervous Necrosis (VNN) infects humpback grouper (Cromileptes altivelis ) as one of the leading export commodities. The purpose of this study was to determine the immune response of kidney and eye tissue receptors for humpback grouper infected by Viral Nervous Necrosis (VNN) through flowcytometric analysis. The method used in this research is descriptive by comparing and analyzing the response of Heat Shock Protein-Hsp70 and TNFα in the kidney and eye tissue of healthy and VNN-infected grouper. The results of the flowcytometric analysis show an immune response in the brain, kidney and eye grouper tissue by the expression of Hsp70 as a stress response to cell and TNF-α as an acute inflammatory response to pathogenic infections. The analysis showed that Hsp70 in healthy grouper fish eye tissue was 8.51%, and VNN infected grouper was 10.90%. Healthy grouper fish kidney tissue was 2.51%, and VNN infected grouper was 8.37%. In comparison, TNF-α in eye tissue was 7.33% in healthy fish and 11.54% in VNN-infected fish, respectively. Then in the kidney tissue was 3.38% in healthy fish and 9.18% in VNN-infected fish. Serious infections can trigger TNF production or induce the expression of Hsp70 in large amounts, causing a systemic reaction. Hsp70 protein can act to protect cells from thermal or oxidative stress and able to induce pro-TNF-α production.